PENERAPAN METODA SER VQUAL DALAM MENINGKATKAN KUALITAS PELAYANAN KIRIMAN EKSPRES DI PT BIROTIKA SEMESTA/DHL - David N. Kaban; Bobby Oedy P. Soepangkat; Sony Sunaryo (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2006)
PT Birotika Semesta/DHL is a courier express company which focuses on international shipment. Very tight competition in parcel delivery industry has forced DHL as a market leader to keep innovating and evaluating their services to the customers. A service that has to be delivered to the customers sometimes does not fulfill their expectation. The courier company itself sometimes has a different perception between services that they have delivered to the customers and customer's expectation of the courier services. This research was designed to measure the customer's satisfaction level using Servqual method Specifically, gap l, between management's perception and customer's expectation, and gap 5, gap between expectation and perception of the customers, were measured. Measurement was done through five dimensions of Servqual, which comprised tangiblity, reliability, responsiveness, assurance, and empathy. The result of this research showed that DHL 's customers could be classified into three clusters according to their level of satisfaction. These clusters comprised customers of whose satisfaction levels were: slightly below their expectation, slightly above their expectation, and far below their expectation. Gap 5 analysis on cluster 1 and 2 resulted in the biggest gap was reliability, and that on cluster 3, the biggest gap was responsiveness. Analysis Gap 1 on cluster 1 and 3 resulted in the biggest gap was responsiveness, and there is no gap on cluster 2. Our suggestion was to focus on responsiveness since this dimension has the biggest gap of all